Mechanical Characteristics of Rice Root–Soil Complex in Rice–Wheat Rotation Area - Huibin Zhu; Haoran Zhao; Lizhen Bai; Shi’ao Ma; Xu Zhang; Hui Li (Agriculture, 2022)
In order to explore the mechanical characteristics of stubble breaking and provide a theoretical basis for the design of a stubble breaking and crushing blockage prevention device, an orthogonal test with three factors (water content, bulk weight, and root content) and a quick shearing test of remolded soil were carried out in a laboratory. The shear resistance of the rice root–soil complex was studied and the soil mechanical equation of the rice root–soil composite was established. It is found that the shear strength of the root–soil composite is related to water content and root content. When the water content was around 30% and the root content was 1.1%, the cohesion of the root–soil composite was the smallest. With the decrease or increase of water content and the decrease or increase of root content, the cohesion of the root–soil composite showed the trend of increasing layer by layer. When the water content was 40% and the root content was 1.1%, the internal friction angle of the root–soil composite showed the minimum value. With the decrease of water content and the increase of root content, the internal friction angle of the root–soil composite gradually showed an increasing trend; while the root content had a great influence on the internal friction angle, the influence of water content on it was relatively small. The direct shear and fast shear tests of root–soil composite samples showed that the shear strength of the root–soil composite and the normal pressure loaded on it conform to the Coulomb equation. The presence of roots increased the shear strength and cohesion value of the soil and improved the resistance to deformation of the soil, but had little influence on the internal friction angle.